An Action Research Study of Promoting Teachers’ Confidence and Competence in Teaching English Meaningfully - Nather, Eiman Hassan (Journal of Education and Training, 2021)
This action research study investigates the introduction, implementation and evaluation of a training course—Meaningful Communication in English (MCE)—designed for English teachers at Saudi public schools. The course aims to promote the teachers’ confidence and competence to use alternatives in classroom practices and develop an English communicative and interactive syllabus. Saudi public schools aim to educate students to use English in real-life communication. However, the current classroom practices do not meet these expectations. Despite having been taught English from Grade 4, most Saudi high school students graduate with low levels of understanding and competence when communicating in English. Saudi teachers and students are afraid of change because they are confused and suspicious about the functions and effectiveness of interactive classroom activities. This situation in schools demands the development of a training course based on communicative and interactive pedagogies and topics related to real life situations. The study is conducted in two cycles to investigate the training strategies and acquisition associated with MCE over 180 hours of training. Each cycle of MCE is based on the themes of the first three stages of research: theme 1- ‘identifying the problem’, theme 2- ‘reviewing literature’ and theme 3- ‘developing a plan’. Upon the completion of MCE in each cycle, participant teachers were encouraged to conduct the following two stages ‘implement the plan’ and ‘evaluate the outcomes’ at their classrooms while providing remote supervision and support. The MCE training course differs from the traditional trainer-directed approach to introducing a learner-centered approach. Two hundred and forty-three English teachers contributed to this study and participated in observations, directed group discussions and surveys. The study found that MCE contributes positively to teachers’ professional confidence and competence. The outcomes from this study will inform current practice and policy in the teaching and learning of English in Saudi Arabian training rooms as well as classrooms, and will contribute to creating an engaging, interactive and learner-centered training courses for the future.